Methods of Large Project Assessment Given Uncertainty in Future Energy Pricing - Kalymon, Basil A. (Management Science, 1981)
The continuing oil crisis has created opportunities for developing sources of oil that had only been marginally economic previously. Many such projects, however, require large-scale investments that are recoverable only over very long lifetimes of operation. The profitability of such investments depends critically on the long-run pricing of oil in world markets and the interaction of the economic conditions of consuming nations. This paper develops a framework for analyzing the economics of such projects. Under the conventional assumption that appropriate levels of compensation for the required capital are needed before such large-scale projects are undertaken, the analysis focuses on the rate of return required to induce the large-scale capital expenditures. Both systematic and non-systematic risk exposure of such projects are identified and the critical linkage to world oil markets is defined through a simple market of world oil pricing. The understanding of the nature of project risks is critical to the development of government policy. The risk exposure of investors must be understood both for the development of risk reduction measures and for the establishment of suitable guidelines for capital compensation. The role of governments in energy investment has escalated and the implications for investments by the private sector require explicit recognition and study. It is shown that the traditional theory of risk pricing through the capital asset pricing model generally leads to conclusions that appear to be contradicted by observed investor behavior. Explanation and understanding of the nature of project risks incurred by the large-scale energy project must rely on more complex, disequilibrium models of risk determination. To illustrate the methodology developed, the paper considers investment in the Canadian tar-sands projects in Western Canada. A sensitivity analysis was performed on the rate of return of this project using simulation. The project was described in terms of both a world oil market and a taxation environment. For the range of conditions investigated, the rate of return was found to range between 4 and 20%, with a mean of 14.3% and a standard deviation of 3.3%.